Untaming girlhoods storytelling female adolescence - Santos, Cristina 1972- (Routledge, 2023)
"This is an interdisciplinary examination of depictions of girlhoods through a comparative study of foundational fairy tales revised in popular narrative, film and television adaptations. The success of franchises such as The Hunger Games, Twilight and Divergence have re-presented the young heroine as an empowered female, and often an action figure in her own right. Through a selection of popular culture touchstones this empowerment is questioned as a manipulation of feminist ideals of equality and a continuation of the traditional vision of female awakening centering on issues of personal choice, physical violence and, purity and beauty. By investigating re-occurring storytelling frameworks and archetypes, Untaming Girlhoods examines different portrayals of girl(hood)s in the 20th- and 21st-century Anglo-American cultural imaginary that configure modern girl(hood)s beyond the fairy tale princess or the damsel in distress-into refigurations that venture away from the well-trodden path for a new breakaway path to selfhood. This will be a useful and enlightening text for students and researchers in Girlhood Studies, Gender Studies, Film Studies and Media Studies"--
Keywords: Geschlechterrolle; Fernsehen; Märchen; Adaption -- Literatur; Motiv; Weibliche Heranwachsende; Film; Mädchen -- Motiv; Geschlechterforschung; Girls in popular culture; Girls in mass media